New retroplumid crabs (Crustacea, Brachyura, Retroplumidae Gill, 1894) from the Eocene of Huesca (Aragón, Spain) - Artal, Pedro; van Bakel, Barry W.m.; Fraaije, René H. B.; Jagt, John W. M. (Zootaxa, 2013)
Two new brachyurans assignable to the family Retroplumidae Gill, 1894, Serrablopluma diminuta n. gen., n. sp., and Gaudipluma bacamortensis n. gen., n. sp., from the Eocene of northern Spain (Huesca, Aragón), substantially enlarge our current knowledge of the morphological diversity of the family. The material, with well-preserved ventral surfaces, per-mits the erection of two new genera that can be referred to the family with confidence on the basis of the general carapace shape, narrow front, a reduced last pair of pereiopods and characteristic thoracic sternum (broad, trapezoidal sternites 3, 4, subrectangular sternites 5–7, sternite 8 conspicuously reduced and inclined). Serrablopluma diminuta n. gen., n. sp. co-occurs with two other retroplumids in the most diverse fossil assemblage of that family known to date.